2001
DOI: 10.1111/j.1752-0606.2001.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Family Systems Therapy for Children in Family Therapy

Abstract: This article presents a developmentally supported implementation of Internal Family Systems Therapy for school-age children and their families. Relevant developmental characteristics of children are described. Suggestions for working with parents, child-oriented interventions, and a case example are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similarly, the third wave cognitiveϪbehavioral therapy approach staunchly relies on the very same postulatesparticularly on attuning to the present while working toward the future-in its recent evidence-based therapeutic versions, aimed at alleviating a wide variety of symptoms and problems (Hayes, 2012a(Hayes, , 2012b. Family systems-and culture-based therapies, with their focus on holism, social justice, and individual empowerment, have been subjected to the soft, albeit persistent, humanistic-existential persuasions (Comas-Diaz, 2012;Satir, 1978;Wark, Thomas, & Peterson, 2001). Of course, the humanistic-existential movement has given the field some priceless, "purified" experiential therapeutic modalities, which have been shown, empirically and compellingly, to ddress multiple symptoms and syndromes (e.g., emotion focus therapy; see Greenberg & Watson, 2006).…”
mentioning
confidence: 99%
“…Similarly, the third wave cognitiveϪbehavioral therapy approach staunchly relies on the very same postulatesparticularly on attuning to the present while working toward the future-in its recent evidence-based therapeutic versions, aimed at alleviating a wide variety of symptoms and problems (Hayes, 2012a(Hayes, , 2012b. Family systems-and culture-based therapies, with their focus on holism, social justice, and individual empowerment, have been subjected to the soft, albeit persistent, humanistic-existential persuasions (Comas-Diaz, 2012;Satir, 1978;Wark, Thomas, & Peterson, 2001). Of course, the humanistic-existential movement has given the field some priceless, "purified" experiential therapeutic modalities, which have been shown, empirically and compellingly, to ddress multiple symptoms and syndromes (e.g., emotion focus therapy; see Greenberg & Watson, 2006).…”
mentioning
confidence: 99%
“…IFS has been a recommended therapeutic approach for various clinical concerns such as eating disorders (Lester, 2017), trauma (Lavergne, 2004; Lucero et al, 2018; Miller et al, 2014), dissociation (Pais, 2009), depression, and chronic pain (Haddock et al, 2017; Shadick et al, 2013). It has also been shown to integrate well with other therapeutic approaches including Eye Movement Desensitization and Reprocessing (Brown, 2020; Twombly & Schwartz, 2008), narrative therapy (Miller et al, 2014), art therapy (Lavergne, 2004), couples therapy (Prouty & Protinsky, 2002), and family therapy (Wark et al, 2001). Additionally, there has been significant, recent research of IFS and its ability to integrate in a multireligious context (Baldwin, 2021; Holmes, 1994; Janes et al, 2023; Yong, 2020).…”
Section: Internal Family Systemsmentioning
confidence: 99%
“…This paper wishes to draw attention to the following research that supports identified therapeutic approaches for future research and consideration. In particular, Dyadic Developmental Practice DDP (Philips, Milim and Hughes, 2020;Hughes, Golding and Hudson, 2019;Bomber, Golding and Philips 2020), Social Neuroscience (Cozolino, 2013), Neurosequential Model in Education (NME) (Perry, 2009), Child -Mentalization Based Treatment (C-MBT) (Bateman and Fonagy, 2013;Twemlow, Fonagy and Sacco, 2005a), Internal Family Systems (IFS) (Swartz and Sweezy, 2019;Spiegel, 2017;Wark, Thomas and Peterson, 2001), Sensorimotor Psychotherapy & Embedded Relational Mindfulness (Ogden, Goldstein and Fisher, 2013;Ogden and Fisher, 2015;Ogden and Goldstein, 2017), Mindsight (Siegel, 2010), The Polyvagal Theory (Porges, 2018;Dana, 2018;Beauchaine, Gatzke-Kopp and Mead, 2017) Attachment (Bowlby, 1970;Ainsworth and Bell, 1970;Main, 2000) and Emotional Freedom Techniques (Clond, 2016;Stapleton et al, 2017;Gaesser, 2020). Future papers would critically analyse the research that suggests implementation would greatly support child mental health and gives strength to the argument that teacher training could potentially include understanding of a number of these therapeutic approaches to improve child mental health outcomes.…”
Section: Transdisciplinary Therapeutic Approaches For Practical Use I...mentioning
confidence: 99%